Changing health-seeking behaviour in the context of development interventions: experiences from Matlab, Bangladesh - Ahmed, Syed Masud; Adams, Alayne M; Chowdhury, Mushtaque; Bhuiya, Abbas (BRAC Research and Evaluation Division (RED), 2019)
It is generally assumed that socioeconomic development interventions will enhance the-material and social capacities of the poor who are disenfranchised to prevent ill health, and to seek appropriate and timely care. Using cross-sectional data from surveys undertaken in 1995 and 1999 as part of the BRAC-ICDDR, B Joint Research Project in Matlab, Bangladesh, this paper explores patterns of health-seeking behaviour over time, with the hypothesis that exposure to integrated socioeconomic development activities will enhance gender equity in care-seeking, and the use of qualified medical care. While there is tentative evidence of greater gender equity in treatment choice among households benefiting from development interventions, a preference for qualified medical care is not apparent. Findings reveal a striking and generalized rise in selftreatment over the four year period that is attributed to the repercussions of a major flood in 1998, and greater heath awareness due to the density of community health workers in Matlab. Also noteworthy is the substantial reliance on informal and often unqualified practitioners (over 20%) such as pharmacists and itinerant drug sellers. Factors associated with the type of health care sought were identified using logistic regression. Self-care is associated with female gender, the absence of low cost health services, and illnesses of relatively short duration. Medical care, on the other hand, is positively predicted by male gender, geographic location, greater socioeconomic status, and serious illness of long duration. The paper concludes by emphasizing the importance of enhancing local capacities to determine whether self-treatment is indicated, to self-treat appropriately, or in cases where health care is sought, to judge provider competence and evaluate whether treatment costs are justified. The provision of training on the rational and informed use of allopathic drugs to the full spectrum of informal health care providers is also recommended.